2006
DOI: 10.1097/01.brs.0000229250.69369.ac
|View full text |Cite
|
Sign up to set email alerts
|

Does Computer-Assisted Spine Surgery Reduce Intraoperative Radiation Doses?

Abstract: These findings are important for the operating room personnel, which is exposed daily to radiation intraoperatively, as well as the patients, when using CAS procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
70
0
11

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(84 citation statements)
references
References 17 publications
3
70
0
11
Order By: Relevance
“…CT-navigation reduces radiation exposure for the patient when the first computed tomography after trauma can be used for planning [10]. The radiation dose increases considerably when an additive CT scan for navigation planning is required.…”
Section: Discussionmentioning
confidence: 99%
“…CT-navigation reduces radiation exposure for the patient when the first computed tomography after trauma can be used for planning [10]. The radiation dose increases considerably when an additive CT scan for navigation planning is required.…”
Section: Discussionmentioning
confidence: 99%
“…Surgeon radiation exposure was less with the mini-C-arm. Gebhard et al [6] performed a prospective study of patients who underwent cervical, thoracic, or lumbar spine fracture fixation with pedicle screws through CT computerassisted navigation, Iso C-arm computer-assisted navigation, or standard C-arm placement. Radiation exposure to the patient was decreased with the use of Iso C-arm computer-assisted surgery.…”
Section: Use Of the Standard C-arm Fluoroscopy Compared With Fluoroscmentioning
confidence: 99%
“…Gebhard [6] Cadaveric comparison study hard to characterize and may always represent an area of uncertainty in studies on this topic. We found that radiation exposure was higher during procedures using less invasive spine approaches than an open approach.…”
Section: Cadaveric Studymentioning
confidence: 99%
“…The radiation exposure of the patients mainly depends on the CT protocol [59][60][61]. By analyzing the radiation of three different CT protocols-based navigation system, Slomczykowski et al [59] noted that when CTNav was to be used, the spiral mode of CT scanning was recommended.…”
Section: Other Perioperative Findingsmentioning
confidence: 99%